Chronic 3-Nitropropionic Acid Treatment in Baboons Replicates the Cognitive and Motor Deficits of Huntington’s Disease - Palfi, Stéphane (J Neurosci, 1996)
We showed recently that chronic administration of the mitochondrial inhibitor 3-nitropropionic acid (3NP) in primates produces various dyskinetic movements and dystonic postures associated with selective striatal lesions displaying many similarities with the pathological features of Huntington’s disease (HD). In the present study, we examined whether such a toxic treatment could also induce frontal-type deficits similar to those observed in HD patients. Cognitive performances of 3NP-treated and control baboons were compared using the object retrieval detour task (ORDT), a test designed to assess the functional integrity of the frontostriatal pathway in human and nonhuman primates. During the same time, the motor function of each animal was assessed under spontaneous “no drug” conditions, and time-sampled neurological observations were used after apomorphine administration. A significant impairment in the ORDT was observed in the 3NP animals after 3–6 weeks of treatment, occurring in the absence of spontaneous abnormal movements but in the presence of apomorphine-inducible dyskinesias. Prolonged 3NP treatment resulted in the progressive appearance of spontaneous abnormal movements. Histological evaluation of these animals showed selective bilateral caudate–putamen lesions with sparing of the cerebral cortex, notably the prefrontal cortex. The present study demonstrates that chronic 3NP treatment replicates in primates the basic pathophysiological triad of HD, including spontaneous abnormal movements, progressive striatal degeneration, and a frontostriatal syndrome of cognitive impairment.